EVALUASI ALAT PENUKAR KALOR (COOLER) DI HIGH VACUUM UNIT (HVU) III (STUDI KASUS DI KILANG XYZ) - Sarah Dampang (JURNAL KONVERSI, 2018)
HVU III is designed to process reduced crude oil from CDU V or reduced crude from export oil existing tanks. HVU III is one unit that aims to lift light fractions that may still be contained in reduced crude. The vacuum condition is designed to attract mild fractions at relatively low temperatures. With the effort to take the product slop wax as HVGO, indeed the operating condition is changing and there is addition of equipment (Pump and HE) and modification of piping. Therefore in this study about design HE (Cooler) with slop wax product as HVGO which will be cooled from temperature 298oC to 70oC with flow rate 40 m3 / hr. And as a cooling medium used Sea Water (sea water) from temperature 30oC to 38oC. Pressure slop wax 20 kg / cm2 and sea water 4 kg / cm2. The calculation results for cooling the wax slop requires a Cooler of 6 (six) units with a seawater requirement of about 709187.39 lb / hr, and heat transferred in a fouled state of 0.0029 hr ft2 F / btu. Pressure drop for slop wax equal to 7.08 psi while sea water equal to 39.33 psi. Under these conditions it is expected that the addition of equipment in this case Cooler can be done as an effort to take the product of slop wax as HVGO.